The Effect of Physical Work Environment and Communication on Employee Job Satisfaction in PT. Razza Prima Trafo Medan - Fauzi; Aminuddin (International Journal of Science, Technology & Management, 2022)
The subject of this research was PT. Razza Prima Transformer Medan, because there was a decrease in employees job satisfaction in the company. Employee satisfaction indicate whether or not the employees feel satisfied working in a company. The decline in employee satisfaction was in a decline in physical working environment that is unfavorable to disturb the concentration of employees at work. On the other hand, the poor communication experienced among employees often occured such as miscommunication of information that lead to errors in the execution of tasks. This study to analyze the effect of the physical working environment and communication on employees job satisfaction at PT. Razza Prima Transformer Medan. The research used a quantitative approach, the type of research was quantitative descriptive, and the nature of the research was explanatory. Data were collected by interviews, questionnaires, and documentation study. Methods of analysis used was linear regression analysis. The populations were 120 employee respondents of PT. Razza Prima Trafo Medan. Samples were drawn by purposive sampling technique that the samples used were 73 employees and 30 employees were used for the validity test which were carried out at the branch of PT. Razza Prima Transformer Medan. The results showed that the physical work environment and communication simultaneously or partially had a significant effect on job satisfaction of employees at PT. Razza Prima Transformer Medan . The results also indicated where the determination coefficient was 29.1%. The study concluded that simultaneously and partially, physical work environment and personal communication have a significant effect on job satisfaction at employees at PT. Razza Prima Transformer Medan.